KONFORMITAS DAN KOHESIVITAS SEBAGAI MANAJEMEN KOMUNIKASI ANTARBUDAYA WARGA TIONGHOA DI KABUPATEN BOGOR - Agus Hitopa Sukma; Misnan Misnan; Iswahyu Pranawukir (Universitas Prof. Dr. Moestopo (Beragama), 2023)
The purpose of research is to know the cultural ethnic cohesiveness in the conformity of local wisdom, a study of social construction and management of intercultural communication among Chinese citizens in Bogor Regency. By using qualitative descriptive method and analysis, the several findings were obtained. First, in the Chinese Village of Inkopad-Inkopol, West Bogor, the cultural cohesiveness has been initiated since the colonial era, through a family approach. The conformity of local wisdom is shown by the involvement of ethnic Chinese in